2012
DOI: 10.1002/agr.21300
|View full text |Cite
|
Sign up to set email alerts
|

Management Control Systems and ISO Certification as Resources to Enhance Internationalization and Their Effect on Organizational Performance

Abstract: There has been a general consensus in recent literature that internationalization is a key success factor in the competitive business environment we now live in. Using a sample of Spanish agri‐food companies, the main objective of this research is to determine the linkage of Management Control Systems (MCS), ISO certifications, internationalization and performance. The results obtained reveal, as expected, that internationalization has a direct and positive relationship with organizational performance. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 66 publications
1
16
0
2
Order By: Relevance
“…However, since companies are likely to have multiple certifications to fulfil their stakeholders' demands it is important to analyse their combined impact on performance (Vastag, 2004). Conde et al (2012) investigated the presence of multiple ISO certifications in the agri-food sector and their impact on performance. They found that organisational performance increased as the number of certifications increased.…”
Section: Performance Implications Of Multiple Certificationsmentioning
confidence: 99%
“…However, since companies are likely to have multiple certifications to fulfil their stakeholders' demands it is important to analyse their combined impact on performance (Vastag, 2004). Conde et al (2012) investigated the presence of multiple ISO certifications in the agri-food sector and their impact on performance. They found that organisational performance increased as the number of certifications increased.…”
Section: Performance Implications Of Multiple Certificationsmentioning
confidence: 99%
“…There is vast, empirical literature which looks into the certification schemes, supply chain management techniques or providing stakeholder's perspective on both issues (Blazovich et al 2014;Conde et al 2013;Fulponi 2006;Grolleau, et al 2007;Kalfagianni 2014). However, it is often regardless of the production activity or purely based on secondary data analyses, difficult to repeat or verify on specific research sample, or verify third-party methodology (Blazovich et al 2014).…”
Section: Empirical Researchmentioning
confidence: 99%
“…Instead, any institutional initiatives introduced by private actors (i.e. firms, society) for governance began to gain ground (Conde et al 2013;Bitzer et al 2013). In other words, it is not only the monetary objectives which are the drivers of the business growth.…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à capacidade de se internacionalizar, a certificação ISO (9001 qualidade, 14001 meio ambiente e 22000 segurança alimentar) demonstrou influenciar positivamente a capacidade de internacionalização. E que a capacidade de internacionalização está positivamente relacionada com o desempenho organizacional (CONDE;. Um estudo realizado no Brasil concluiu que as empresas com um sistema de gestão ambiental certificado de acordo com a norma ISO14001 tendem a ser mais rentáveis, em média, do que as empresas sem certificação (FERRON;.…”
Section: Adoção De Sistemas De Gestão Ambiental/socialunclassified